ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA GURU DITINJAU DARI FAKTOR DEMOGRAFI - MIRA ARIYANI; DESTY ZULKARNAIN (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
The objectives of the study were to determine the differences of Organizational Citizenship Behavior (OCB) based on the Extra-role Behavior (OCB) dimensions of the teachers in terms of demographic factors (gender, age, marital status, and employment status). The samples are 138 primary school teachers in districs Duren Sawit, East Jakarta. The study used the Organizational Citizenship Behavior (OCB) scale of the adoption of the Extra-role Behavior (ERB) consisting of 18 items with the reliability Î±lpha = 0.91. The conclusion is that there is a difference Organizational Citizenship Behavior (OCB) with dimension of Extra-role Behavior (ERB) student in teacher by demography factors (marital status and employment status), dimension of Extra-role Behavior (ERB) team on teacher by demography factor (age, marital status and employment status), and dimension of Extra-role Behavior (ERB) organization on teachers by demographic factors (employment status).